2002
DOI: 10.1523/jneurosci.22-21-09635.2002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That 5-HT2AReceptors in the Hypothalamic Paraventricular Nucleus Mediate Neuroendocrine Responses to (−)DOI

Abstract: The present study determined whether the serotonin2A (5-HT2A) receptors in the hypothalamic paraventricular nucleus mediate the neuroendocrine responses to a peripheral injection of the 5-HT2A/2C receptor agonist (-)DOI [(-)1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane]. The 5-HT2A receptor antagonist MDL100,907 ((+/-)-alpha(2,3-dimethoxyphenyl)-1-[2-(4-fluorophenylethyl)]-4-piperidinemethanol), the 5-HT2C receptor antagonist SB-242084 (6-chloro-5-methyl-1-[[2-[(2-methyl-3-pyridyl)oxy]-5-pyridyl]carbamoyl]-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 51 publications
3
61
0
2
Order By: Relevance
“…In the present study, the (â)DOI-evoked release of corticosterone and prolactin was greater in rats undergoing cocaine withdrawal, a result that is consistent with reports in the literature (Baumann et al, 1993;Baumann and Rothman, 1998;Levy et al, 1992). We have previously reported that the neuroendocrine effects of (â)DOI, are mediated exclusively by activation of 5-HT 2A receptors (but not 5-HT 2C receptors) in the PVN (Zhang et al, 2002). Consequently, the potentiated responses to (â)DOI of two different hormones (prolactin and corticosterone) that are mediated by distinct signaling pathways suggests supersensitivity mediated at the level of 5-HT 2A receptor signal transduction.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the (â)DOI-evoked release of corticosterone and prolactin was greater in rats undergoing cocaine withdrawal, a result that is consistent with reports in the literature (Baumann et al, 1993;Baumann and Rothman, 1998;Levy et al, 1992). We have previously reported that the neuroendocrine effects of (â)DOI, are mediated exclusively by activation of 5-HT 2A receptors (but not 5-HT 2C receptors) in the PVN (Zhang et al, 2002). Consequently, the potentiated responses to (â)DOI of two different hormones (prolactin and corticosterone) that are mediated by distinct signaling pathways suggests supersensitivity mediated at the level of 5-HT 2A receptor signal transduction.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, in the BLA, where 5-HT boutons form synapses, 5-HT2A, 5-HT2C, and 5-HT3 receptors are the main receptors (Wright et al, 1995;McDonald and Mascagni, 2007;Muller et al, 2007). 5-HT2A and 5-HT2C receptors are also strongly expressed in the hypothalamic paraventricular nucleus and intralaminar thalamic nuclei, with preserved innervation in the Pet1 knock-out (Zhang et al, 2002;Heisler et al, 2007).…”
Section: Pet1-resistant 5-ht Neurons Define a Subsystem Embedded In Tmentioning
confidence: 99%
“…The neuroendocrine response to serotonergic activation has been used as a diagnostic tool to examine the functioning of serotonergic neurons in the brains of patients suffering from mood disorders (Lerer, et al, 1999). The presence of 5-HT 2A receptors in the hypothalamic PVN is supported by autoradiographic (Appel, et al, 1990), in situ hybridization (Gundlah, et al, 1999;Wright, et al, 1995) and immunohistochemical labeling studies (Zhang, et al, 2002). 5-HT 2A receptors in the hypothalamic PVN mediate the neuroendocrine responses to an acute peripheral injection of the selective 5-HT 2A/C receptor agonist, DOI.…”
Section: Introductionmentioning
confidence: 99%
“…5-HT 2A receptors in the hypothalamic PVN mediate the neuroendocrine responses to an acute peripheral injection of the selective 5-HT 2A/C receptor agonist, DOI. This was demonstrated using both intra-PVN and peripheral injections of the selective 5-HT 2A receptor antagonist MDL 100,907 which dose-dependently inhibited the effect of DOI (1 mg/kg, s.c.) on hormone secretion (HemrickLuecke and Evans, 2002; Van de Kar, et al, 2001;Zhang et al, 2002). Thus, plasma hormone levels can be used as an index of the function of 5-HT 2A receptor signaling in the hypothalamic PVN.…”
Section: Introductionmentioning
confidence: 99%